Myrmotherula Antwrens (Aves, Formicariidae) as army ant followers - Willis, Edwin O. [UNESP] (Sociedade Brasileira de Zoologia, 1983)
Antwrens of the genus Myrmotherula (Formicariidae) are common members of mixed flocks in the understory of neotropical forest, but rarely follow army ants more than a few minutes as a flock passes. Antwrens that glean in open foliage (axillaris, longipennis) and ones that forage on dead foliage (fulviventris and relatives) apparently have to canvass large areas too rapidly to stay with slow-moving ants. Antwrens that glean low foliage of vertical seedlings (guttata, hauxwelli, gularis) can stay near ants only in such patches, despite close resemblance to sallying and hence less microhabitat-limited Hylophylax antbirds, some of which follow ants regularly.